(untitled) (LACCEI, 2024)
The objective of the study was to analyze the cyanidation leaching processes of the companies with the highest gold production in Peru. The approach was descriptive, in which bibliographic records were searched and retrieved from different relevant and reliable sources of information, which were analyzed using graphs and tables to classify the information. It was obtained that the main gold producing companies that used the cyanidation leaching process in 2021 were: Compañía Minera Poderosa S.A, Minera Yanacocha S.R.L., Minera Aurífera Retamas S.A., Consorcio Minero Horizonte S.A., Compañía Minera Ares S.A.C. and Shahuindo S.A.C. with 856 003 552 723 528 537 531 027 452 088 and 485 941 grams of fine gold respectively also the highest plant capacity was reported by Minera Yanacocha S.R.L. with 87 000 MT/day on the other hand Compañía Minera Poderosa S.A. reported the highest head grade and recovery of 17.89 g/t Au and 91.84 % respectively all the mining companies identified use the cyanide leaching process and most of them use the Merrill Crowe process for gold precipitation. It was concluded that Compañía Minera Poderosa is the largest gold producer at national level, and reached its highest production in 2019 being 314 thousand oz of Au, also in that year it obtained its highest head grade which was 19.17 g/t Au.